Experiences in learning research methods: Recommendations from undergraduate nursing students at two African universities - Florence Mbuthia; L.J. Mogakwe; Champion Nyoni; Marianne Reid; Winfred Wambui; Simon Githui (Elsevier, 2024)
Background: Globally there is increasing demand for high-quality nursing care driven by research and evidence-based practice. Engagement of undergraduate nursing students in research activities identifies experiences and strategies that bring best outcomes in nursing practice. This study sought to establish strategies that will improve research practices among undergraduate nursing students at two African universities. Methods: The study was conducted in University of the Free State (UFS) in South Africa and Dedan Kimathi University of Technology (DeKUT) in Kenya. Nominal group technique (NGT) was used to collect data from 116 undergraduate nursing students (South Africa = 53; Kenya = 63). Participants recruitment involved complete collection sampling with 5 group discussions (South Africa = 2; Kenya = 3). Data analysis involved initial intra-group analysis step done to tally and combine scores for specific ideas. Second step identified top five ideas across groups per institution based on highest scores. Final step compared similarities and differences between the two institutions. Ethical clearance was obtained in both countries. Results: The nominal group results showed top five priorities for the students in Kenya were group work research, calm manner of addressing mistakes, timely feedback from supervisors, standardised assessment, face to face teaching of data analysis software and avoidance of nullification of research projects. South African university students prioritised Student support, knowing expectations, supervisor's feedback and contact classes, interactive classrooms and breaking down research jargon. Conclusion: The participants reported need for creating supportive learning experiences with peer/teacher mentorship. Timely feedback, structured supervision, and student-centred approach to learning new information in research enrich learners' positive experience.